DEVELOPMENT OF MICRO-HYDROELECTRIC GENERATION SYSTEM FROM WATER PIPELINE - LEITÃO MUANDO, VIRGÍLIO (Universiti Teknologi PETRONAS, 2012)
Utility water is normally stored in enormous tanks placed at certain height from the ground for distribution. This water, when exiting the tank, develops an increasing kinetic energy as it goes through the pipeline to its end usage. The kinetic energy that builds up is not being completely used. The research presented in this report focuses on harvesting energy from water in main pipelines (1), developing a micro-hydroelectric generation system from main pipeline (2) and conducting dynamic tests for the system (3). Numerous cost-effective and practical ideas are discussed with the aim of meeting different reliable power system dynamic characteristics such as frequency and voltage stability. A pumped-storage pico hydro generation scheme using a permanent magnet synchronous generator (PMSG) is assembled as a platform for conducting dynamic tests of the system. Issues regarding grid-connected and off-grid generation as well as reliability of the sustainable generation are addressed according to the results summarized from experiments and tests.